STRATEGI PENGEMBANGAN EKONOMI KREATIF MELALUI KEARIFAN LOKAL SEBAGAI PENUNJANG DAYA TARIK WISATA - Benedhikta Kikky Vuspitasari; Yeremia Niaga Atlantika (POLITEKNIK LP3I JAKARTA, 2024)
The aim of the research is to provide an overview of creative economy development strategies and programs based on local wisdom in Bengkayang Regency. This descriptive qualitative research was conducted in Bengkayang Regency. The research subjects are the government, community, creative business owners, and visitors. Researchers use data collection methods such as interviews, observation, documentation, and literature studies for the purpose of looking at phenomena as a whole and partially. By using a qualitative descriptive approach, the researcher wants to examine the object as a whole by collecting data in the form of information, observation notes, and narrative interviews. The research results are based on SWOT analysis. The development of tourism in Bengkayang cannot be separated from the existence of rich culture in the local area. To be able to find out the strategies used to develop cultural tourism in Bengkayang, a potential analysis is needed by mapping strengths to be able to take advantage of cultural tourism opportunities in Bengkayang. The factors that need to be considered in developing microareas in Brape Sawa activities so that they are economically feasible are as follows: taking into account the physical and non-physical environment of the area and culture as important resources to consider so that they can be recognized by the younger generation, Promotion of tourism using information technology through print and electronic media, collaboration opens up opportunities to improve the quality of cultural tourism in Bengkayang, but is supported by government policy by increasing and encouraging the role of local investment.